Dose Reconstruction for the Million Worker Study. Issue 2 (February 2015) - Bouville, André; Toohey, Richard E.; Boice, John D.; Beck, Harold L.; Dauer, Larry T.; Eckerman, Keith F.; Hagemeyer, Derek; Leggett, Richard W.; Mumma, Michael T.; Napier, Bruce; Pryor, Kathy H.; Rosenstein, Marvin; et al.
<x xml:space="preserve">Abstract</x> Abstract The primary aim of the epidemiologic study of one million U.S. radiation workers and veterans [the Million Worker Study (MWS)] is to provide scientifically valid information on the level of radiation risk when exposures are received gradually over time and not within seconds, as was the case for Japanese atomic bomb survivors. The primary outcome of the epidemiologic study is cancer mortality, but other causes of death such as cardiovascular disease and cerebrovascular disease will be evaluated. The success of the study is tied to the validity of the dose reconstruction approaches to provide realistic estimates of organ-specific radiation absorbed doses that are as accurate and precise as possible and to properly evaluate their accompanying uncertainties. The dosimetry aspects for the MWS are challenging in that they address diverse exposure scenarios for diverse occupational groups being studied over a period of up to 70 y. The dosimetric issues differ among the varied exposed populations that are considered: atomic veterans, U.S. Department of Energy workers exposed to both penetrating radiation and intakes of radionuclides, nuclear power plant workers, medical radiation workers, and industrial radiographers. While a major source of radiation exposure to the study population comes from external gamma- or x-ray sources, for some of the study groups, there is a meaningful component of radionuclide intakes that requires internal radiation dosimetry assessments. Scientific Committee 6–9 has been established by the National Council on Radiation Protection and Measurements (NCRP) to produce a report on the comprehensive organ dose assessment (including uncertainty analysis) for the MWS. The NCRP dosimetry report will cover the specifics of practical dose reconstruction for the ongoing epidemiologic studies with uncertainty analysis discussions and will be a specific application of the guidance provided in NCRP Report Nos. 158, 163, 164, and 171. The main role of the Committee is to provide guidelines to the various groups of dosimetrists involved in the MWS to ensure that certain dosimetry criteria are considered: calculation of annual absorbed doses in the organs of interest, separation of low and high linear-energy transfer components, evaluation of uncertainties, and quality assurance and quality control. It is recognized that the MWS and its approaches to dosimetry are a work in progress and that there will be flexibility and changes in direction as new information is obtained with regard to both dosimetry and the epidemiologic features of the study components. This paper focuses on the description of the various components of the MWS, the available dosimetry results, and the challenges that have been encountered. It is expected that the Committee will complete its report in 2016.